Tumour lysis in newborn: spontaneous or secondary to antenatal steroids?. (4th April 2018) - Ponmudi, Nithya J; Beryl, Shafini; Santhanam, Sridhar; Beck, Manisha
Abstract : Malignancies are rare in the early neonatal period. Common congenital tumours include malignant teratoma and neuroblastomas. Tumour lysis syndrome is a serious condition usually seen after commencement of chemotherapy for a malignancy. Rare case reports of spontaneous tumour lysis have been reported though not in the newborn period. We report here an instance of tumour lysis syndrome in a newborn with congenital rhabdoid tumour, where the cause was either spontaneous or related to antenatal steroid exposure.